Experimental study on seismic behavior of reinforced concrete shear walls with low shear span ratio. (January 2022) - Wei, Feng; Chen, Honghua; Xie, Yuejun
Abstract: Shear span ratio (SSR) is a key factor affecting the structural and seismic behavior of shear walls. Existing experimental studies on the seismic behavior of shear walls with SSR less than 1.0 are limited. In order to study the seismic behavior of squat reinforced concrete (RC) shear walls, 16 specimens (of which four specimens were subjected to coupled tension-shear force) with SSR of 0.5, 0.75, and 1.0 were fabricated and subjected to horizontal low-cycle repeated loading tests. The parameters considered in the test included the SSR, axial load ratio (ALR), and horizontal reinforcement ratio (HRR). The seismic behavior of the 16 squat RC shear wall specimens was investigated by analyzing their failure modes, hysteretic behaviors, and energy dissipation capacities. This study also assessed the validity of shear strength capacity formulae for shear walls with low SSR adopted in the design codes used currently in China, America, Canada and Europe. Five failure modes were observed in the 16 specimens, namely, diagonal compression-sliding (DCS) failure, diagonal compression (DC) failure, shear-bending (SB) failure, shear sliding (SS) failure, and tensile shear (TS) failure. For the specimens under compression, the failure mode of the specimens changed from shear failure to shear-bending failure with the increase in SSR. Also, the shear strength capacity was significantly reduced as SSR increased, while the deformation capacity and energy dissipation capacity increased significantly. The specimens under tension with SSR of 0.5 suffered TS failure. Vertical tension significantly decreased the shear strength capacity and energy dissipation capacity of the shear walls, however their ductility factor and ultimate displacement increased. The increase in ALR from 0.3 to 0.5 enhanced the shear strength capacity of the shear walls but the energy dissipation capacity reduced. With the increase in HRR, the shear strength capacity and energy dissipation capacity of the shear walls improved slightly. The shear strength capacities of shear walls assessed according to the four design codes were all conservative for the specimens suffering DC failure and DCS failure, while the opposite was true for the specimens with TS failure. For the specimens suffering SB failure, only the ACI 318-19 calculation results were not conservative compared to the test results. Highlights: 16 shear wall specimens with shear span ratio less than 1.0 were tested. The seismic behavior of squat walls under compression/tension was explored. Squat shear walls under coupled tension-shear force suffered tensile shear failure. The validity of design provisions for squat walls in four codes was investigated.